Optimalisasi Alokasi Sumberdaya Pada Sistem Usahatani Lahan Kering di Desa Kerta, Gianyar, Bali: Pendekatan Linear Programming - Antara, Made; Suardika, Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 1, Februari 2014 (pp. 1-82), 2014)
The objective of the research are (1) to analyze the gross margin in dryland farming systems, (2) to analyze the optimal allocation of agricultural resources in the horticulture farming  and  cattle system in dry land, (3) to determine the effect of changes in the prices of some agricultural commodities to resource allocation in a mixed farming system of  horticulture and cattle on dryland in Kerta Village, Payangan District, Gianyar Regency. Primary data were obtained through a survey of 34 dryland farmers. Constraints optimization analysis in dryland farming systems with linear programming approach using software BLPX 88. Results of the research showed that the gross margin received an average farmer in the Kerta Village before optimization of Rp 47.783.346,00. This gross margin is derived from citrus farming area of ??0.15 ha; elephant grass area of ??0.11 ha; chili first planting season ( musin tanam, MT1 ) covering an area of ??0.09 ha; chili third planting season ( MT3 ) area of ??0.06 ha; tomatoes first planting season ( MT1 ) area 0.07 ha; tomatoes second planting season ( MT2 ) area of ??0.05 ha; tomatoes third planting season (MT3) area of ??0.11 ha; chicory second planting season ( MT2 ) area of ??0.03 ha; beans first planting season ( MT1 ) area of ??0.02 ha; beans second planting season ( MT2 ) area of ??0.14 ha; corn first planting season ( MT1 ) area of ??0.09 ha ; corn second planting season ( MT2 ) area of ??0.05 ha; corn third planting season ( MT3 ) area of ??0.03 ha; sweet potatoes second planting  season (MT2) area 0.04 ha; sweet potatoes third planting season ( MT3 ) area 0.07 ha; peanuts first planting season ( MT1 ) area 0.11 ha; peanut third planting season ( MT3 ) area 0, 10 ha, and maintains five head of cattle. Optimal dryland farming systems in the Kerta Village, generating maximum gross margin  of Rp 49.404.260,00 increased by 3.39% compared to gross revenue of farmers before optimal are Rp 47,783,346.00. Gross margin was obtained from a combination of citrus farming activities area 0.15 ha; elephant grass area of ??0.11 ha; chili first planting season (MT1) area of ??0.09 ha; chili third planting season (MT3) area of ??0.06 ha; tomatoes first planting season (MT1) area 0, 07 ha; tomatoes second planting season (MT2) area of ??0.05 ha; tomatoes third planting season (MT3) area of ??0.11 ha; chicory second planting season (MT2) area of ??0.03 ha; beans first planting season (MT1) area of ??0.02 ha; beans second planting season (MT2) area of ??0.14 ha; corn first planting season (MT1) area 0.09 ha; corn second planting season (MT2) area of ??0.05 ha; corn third planting season (MT3) area of ??0.03 ha; sweet potatoes second planting season (MT2) area 0.04 ha; sweet potatoes third planting season (MT3) area 0.07 hectares, peanuts first planting season (MT1) area ??0.0975 ha; peanut third planting season (MT3) area 0, 0975 ha, and maintains five head of cattle. Decline in the price of red peppers and tomatoes cause changes in the allocation of land use for the red chili and peanuts. whereas if there is an increase in the price of red peppers and tomatoes do not cause changes in resource allocation. Increased peanut prices cause changes in the allocation of land use for land peanuts, red peppers and sweet potatoes while if prices decline peanuts cause changes in land allocation peanuts. When the cow is able to maintain up to eight tails, there will be an increase in farmers' income by Rp 11.110.954, 00 (23,25%). Farmers need to apply the optimal combination of farming activity, so that a maximum income of farmers.
Keywords: optimisation; dry-land farming; gross margin